High-LET Proton Irradiation Significantly Alters the Clonogenic and Tumorigenic Potential of Human Breast Cancer Cell Lines In Vitro and In Vivo - Margarita Pustovalova; Rita Mohammad; Yuzhe Wang; Wenyu Xue; Philipp Malakhov; Viktor Nekrasov; Elizaveta Kontareva; Zain Nofal; Vyacheslav Saburov; Dmitry Kolesov; Andreyan Osipov; Sergey Leonov (Frontiers in Bioscience-Landmark)
Background: The implementation of proton beam irradiation (PBI) for breast cancer (BC) treatment is rapidly advancing due to its enhanced target coverage and reduced toxicities to organs at risk. However, the effects of PBI can vary depending on the cell type. This study aimed to explore the effects of PBI on two BC cell lines, MCF7 and MDA-MB-231. Methods: The relative biological effectiveness (RBE) of PBI was assessed using a clonogenic assay. DNA double-strand break (DSB) repair, epithelial–mesenchymal transition (EMT), and filamentous actin (F-actin) were evaluated using immunofluorescence analysis. The extent of entosis and the senescence-associated β-galactosidase (SA-β-gal) activity were estimated by cytochemistry analysis. The influence of the extracellular matrix was evaluated by cultivating cells in both adherent two-dimensional (2D) environments and within 3D fibrin gels of varying stiffness. The metastatic propensity of cells was investigated using migration tests and the cell encapsulation of carboxylate-modified fluorescent nanoparticles. The comparative tumorigenic potential of cells was investigated using an in vivo model of the chick embryo chorioallantoic membrane (CAM). Results: PBI demonstrated superior efficacy in eliminating MCF7 and MDA-MB-231 cells with RBE 1.7 and 1.75, respectively. Following PBI, MDA-MB-231 cells exhibited significantly lower clonogenic survival compared to MCF7, which was accompanied by the accumulation of phosphorylated histone H2AX (γH2AX), p53-binding protein 1 (53BP1) and Rad51 foci of DNA DSBs repair proteins. After surviving 7 days post-PBI, MCF7 cells exhibited 2.5-fold higher levels of the senescence phenotype and entosis compared to the MDA-MB-231 offspring. Both PBI-survived cell lines had greater capability for 2D collective migration, but their metastatic potential was significantly reduced. A significant influence of extracellular matrix stiffness on the correlation between F-actin expression in PBI-survived cells—an indicator of cell stiffness—and their ability to uptake nanoparticles, a trait associated with metastatic potential, was observed. PBI-survived MDA-MB-231RP subline exhibited a hybrid EMT phenotype and a 70% reduction in tumor growth in the in vivo model of the chick embryo CAM. In contrast, PBI-survived MCF7RP cells exhibit mesenchymal-to-epithelial transition (MET)-like features, and their in vivo tumor growth increased by 66% compared to parental cells. Conclusions: PBI triggers various cellular responses in different BC cell lines, influencing tumor growth through mechanisms like DNA damage repair, stress-induced premature senescence (SIPS), and alterations in the stiffness of tumor cell membranes. Our insights into entosis and the effect of extracellular matrix stiffness on metastatic propensity (nanoparticle uptake) enhance the understanding of the role of PBI in BC cells, emphasizing the need for more research to optimize its therapeutic application.